2003
DOI: 10.3390/80100074
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Synthesizing Partially Substituted Cucurbit[n]uril

Abstract: A novel approach to cucurbituril synthesis is described where partial substitution is introduced into cucurbit[n]uril. The identification of homologues (and their substitution) in reaction mixtures is achieved by a combination of ESMS and the use of the molecular probes (guests) 1,4-dioxane and 1,9-octanediamine. A unique symmetrical hexamethylcucurbit[3,3]uril, the major product, was isolated and characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
225
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(227 citation statements)
references
References 14 publications
0
225
0
2
Order By: Relevance
“…196 We also investigated the condensation of II-3 with II-4, II-3 with II-7, and II-3 with II-9 in hopes of isolating new CB[n] derivatives. 189,197 Unfortunately, we did not detect any doublets at 5. formation in the crude reaction mixture was the presence of characteristic doublets at 5.5 ppm and 4.7 ppm with coupling constants 11 Hz, which are due to the diastereotopic methylene C-H's from II-4, that do not completely disappear during the reaction. We hypothesize that the anhydrous acidic conditions employed -to avoid potential saponification of the CO 2 Et groups -slows down the S-to C-shaped isomerization of trimeric and higher oligomers which results in oligomer formation rather than macrocyclization.…”
Section: X-ray Crystal Structures Of Building Blocks Ii-5 and Ii-7mentioning
confidence: 90%
See 1 more Smart Citation
“…196 We also investigated the condensation of II-3 with II-4, II-3 with II-7, and II-3 with II-9 in hopes of isolating new CB[n] derivatives. 189,197 Unfortunately, we did not detect any doublets at 5. formation in the crude reaction mixture was the presence of characteristic doublets at 5.5 ppm and 4.7 ppm with coupling constants 11 Hz, which are due to the diastereotopic methylene C-H's from II-4, that do not completely disappear during the reaction. We hypothesize that the anhydrous acidic conditions employed -to avoid potential saponification of the CO 2 Et groups -slows down the S-to C-shaped isomerization of trimeric and higher oligomers which results in oligomer formation rather than macrocyclization.…”
Section: X-ray Crystal Structures Of Building Blocks Ii-5 and Ii-7mentioning
confidence: 90%
“…The synthesis of CB[n] analogues is carried out using a building block approach which allows for control over size, shape, and solubility of the resulting macrocycles. 175,186,189,197,212 The X-ray crystal structure of CB [6] analogue III-1, illustrates the elongated shape of the CB [6] analogues (Figure 2) analogues are preorganized to recognize guests molecules through a wide range of non-covalent interactions and are fluorescent. These host molecules, therefore, define a versatile platform to study the binding properties of a wide variety of chemically and biologically important guest molecules including alkyl amines, aryl amines, dyes, amino acids, peptides, and nucleotides using fluorescence spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1) [14][15][16][17]. Recently some efforts have been made to introduce substitution in order to achieve ready solubility in both aqueous systems and common organic solvents, and a number of fully and partially substituted Q[n]s have been reported [18][19][20][21][22][23]. Decamethylcucurbit [5]uril (Me 10 Q [5]) was the first fully substituted Q[n] discovered in 1992 by Stoddart and co-workers [19].…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of cucurbit[n]uril (Q[n]s) has expanded dramatically with the discovery of cucurbituril(Q [6]) and its homologues (Q [5], Q [7], Q [8], and Q [10]) [1][2][3]. Recently, the direct functionalization of CB[n] [4][5][6] and introduction of building blocks for the preparation of Q[n] derivatives [7][8][9] and analogues [10][11] providing CB[n]s with solubility in both organic and aqueous solution has further expanded the range of the research and applications, which have been summarized in related reviews [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the direct functionalization of CB[n] [4][5][6] and introduction of building blocks for the preparation of Q[n] derivatives [7][8][9] and analogues [10][11] providing CB[n]s with solubility in both organic and aqueous solution has further expanded the range of the research and applications, which have been summarized in related reviews [12][13][14][15][16][17][18][19]. More recently, we have found that the solubilities of substituted cucurbit[n]urils (SQ[n]s) are dependent upon the kind, position and number of substituent groups on the substituted cucurbit[n]urils Q[n]s [20].…”
Section: Introductionmentioning
confidence: 99%